Emergent Virus Reactivation in SARS-CoV-2-Negative Community Acquired Pneumonia Patients During the COVID-19 Pandemic - Qu, Junyan; He, Fang; Li, Huan; Lv, Xiaoju (Frontiers in Microbiology, 2022)
Emergent viruses (namely, HSV-1, CMV and EBV) reactivation were common in critically ill patients and/or immunosuppressed patients. This study aimed to understand the clinical manifestations and reactivation of the emergent viruses in SARS-CoV-2-Negative community acquired pneumonia (CAP) patients during the COVID-19 pandemic. We retrospectively reviewed the medical records of CAP patients from Jan to Mar, 2020 in our university hospital in China. The patients were divided into two groups based on the presence or absence of emergent viruses. In all patients, the positive rates of EBV, HSV and CMV were 23.43% (15/64), 22.06% (15/68) and 12.50% (8/64), respectively. The most common presenting symptoms were fever (98, 57.99%) and dry cough (55, 32.54%). The levels of albumin, hemoglobin, lymphocyte count and CD4+ T lymphocyte count in emergent viruses positive group were lower than those of viruses negative group (P < 0.05). The initial chest CT features of these patients were diverse. The most common manifestations were ground-glass opacity (91/169, 53.85%) and pulmonary nodule (88/169, 52.07%). More emergent viruses positive patients have bilateral upper lobes involvement than emergent viruses negative patients (P＜0.05). A total of 80.47% patients (136/169) received empirical antimicrobial treatment. The most commonly used antibiotic regimen was fluoroquinolone monotherapy (80/169, 47.34%). The emergent viruses positive patients have poorer clinical outcome (P＜0.05). In conclusion, emergent viruses reactivation was common in SARS-CoV-2-Negative CAP patients. Emergent viruses positive patients have poorer cellular immune function, more severer conditions and poorer prognosis. Fluoroquinolones may be a therapeutic option for CAP patients.